1990
DOI: 10.1002/jcp.1041430220
|View full text |Cite
|
Sign up to set email alerts
|

Precocious induction of tyrosine aminotransferase mRNA by hydrocortisone in cultured fetal rat hepatocytes at different developmental stages

Abstract: Tyrosine-aminotransferase (TAT) is encoded by a liver-specific gene known to be expressed perinatally. Fetal rat hepatocytes (gestation day 19) in primary cultures, in which TAT gene expression is normally undetectable, are induced by hydrocortisone to express TAT-mRNA in a dose-dependent manner (greater than 10(-7) M). In hepatocytes incubated with hydrocortisone, TAT-mRNA levels were marginal after 24 hours, reaching maximal levels at 48 hours. After a pre-incubation of hepatocytes for 24 hours in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Appropriate controls showed that in cultured normal fetal hepatocytes the TAT and the MT-I genes gained the competence for glucocorticoid induction (Figure 3b), thus resembling the situation in newborn animals. This indicates that the defined culture conditions used here supported the maintenance and the 'maturation' of the hepatocyte phenotype (Hoffmann and Paul, 1990) mRNA levels of genes expressed in livers of newborn normal (cfh) and homozygous deletion mutant (C14C6S) mice. The experiments were carried out as described in Materials and methods.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Appropriate controls showed that in cultured normal fetal hepatocytes the TAT and the MT-I genes gained the competence for glucocorticoid induction (Figure 3b), thus resembling the situation in newborn animals. This indicates that the defined culture conditions used here supported the maintenance and the 'maturation' of the hepatocyte phenotype (Hoffmann and Paul, 1990) mRNA levels of genes expressed in livers of newborn normal (cfh) and homozygous deletion mutant (C14C6S) mice. The experiments were carried out as described in Materials and methods.…”
Section: Resultsmentioning
confidence: 63%
“…Transcription in normal and c 14CoS fetal hepatocytes in primary culture Previous studies had indicated that fetal hepatocytes in primary culture undergo differentiation and 'maturation' leading to precocious induction of the TAT gene in response to hydrocortisone (Hoffmann and Paul, 1990;Shelly et al, 1989). Therefore we examined the transcriptional patterns of cultured primary fetal hepatocytes from normal and cJ4CoS mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fetal rat hepatocytes proliferate in primary culture in response to epidermal growth factor (EGF) and insulin, 1-3 whereas dexamethasone or hydrocortisone and glucagon have been implicated in the regulation of the maturation of these rat hepatocytes. [4][5][6] GGTase (E.C.2.3.2.2), a membrane-bound enzyme indirectly involved in transport of aminoacids and peptides across the membrane, [7][8] was found to be significantly high in rat fetal livers and low in adults. [9][10][11] In vivo, GGTase activity was shown to increase during proliferation of hepatocytes after D-galactosamine injury.…”
Section: Introductionmentioning
confidence: 99%